2008
DOI: 10.1002/eji.200737518
|View full text |Cite
|
Sign up to set email alerts
|

Phage display‐derived recombinant antibodies with TCR‐like specificity against α‐galactosylceramide and its analogues in complex with human CD1d molecules

Abstract: The glycolipid a-galactosylceramide (a-GalCer) is a potent activator of invariant natural killer T (iNKT) cells and has been shown to be an effective agent against cancer, infections and autoimmune diseases. The effectiveness of a-GalCer and its alkyl chain analogues depends on efficient loading and presentation by the antigen-presenting molecule CD1d. To monitor the ability of CD1d to present the glycolipids, we have used a phage display strategy to generate recombinant antibodies with T cell receptor-like (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…To ensure a single iNKT-TCR per QD, the iNKT-TCR-QD conjugate was prepared in an excess of free biotin to occlude SAV-QD excess binding sites. As another control to rule out any potential cross-linking effects induced by the SAV-QD multivalency, we also used the α-GalCer-hCD1d-specific Fab fragment (Fab9b) (9,28,29) covalently attached to the small dye Atto647N. As a third control for the iNKT-TCR probe, α-GalCer-loaded hCD1d molecules were labeled using a monovalent anti-CD1d Ab (CD1d42) conjugated to a QD under excess of free biotin.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure a single iNKT-TCR per QD, the iNKT-TCR-QD conjugate was prepared in an excess of free biotin to occlude SAV-QD excess binding sites. As another control to rule out any potential cross-linking effects induced by the SAV-QD multivalency, we also used the α-GalCer-hCD1d-specific Fab fragment (Fab9b) (9,28,29) covalently attached to the small dye Atto647N. As a third control for the iNKT-TCR probe, α-GalCer-loaded hCD1d molecules were labeled using a monovalent anti-CD1d Ab (CD1d42) conjugated to a QD under excess of free biotin.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggested that short or polyunsaturated lipids failed to efficiently traffic to the lysosome (14,15) but this has not been tested for ␣GC variants. While the variants could directly load CD1d molecules at the cell surface without trafficking to endosomal compartments (5,12,13), lysosomal loading might be required for access to membrane rafts and efficient T-cell stimulation (16).…”
mentioning
confidence: 99%
“…Antibodies with TCR-like binding properties exist for all MHC molecules that present antigens to T cells, including MHC class I (44 -47), MHC class II (48), as well as CD1d (36,49), and are widely used to study or modulate T cell function by specifically blocking antigen-mediated TCR activation. High affinity antibodies that exhibit superior binding affinity are especially useful to block T cell activation and as such have therapeutic potential in various T cell-mediated diseases (46).…”
Section: Discussionmentioning
confidence: 99%